Pengukuran dan Mitigasi Risiko Pada Pembiayaan Murabahah (Studi Kasus : BMT XYZ Surabaya) - Ivantri, Madha Adi; Septiarini, Dina Fitrisia (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This study aimed to find out how much the risk and how is mitigation strategy of murabahah financing risk in BMT XYZ Surabaya. This study used qualitative research. Financing risk measuring use Value at Risk (VaR) approach and use historical data of murabahah financing period in 2012.The result shows that expected loss period in December reached Rp5.888.790,00. Unexpected Loss such as VaR at confidence lavel 99%period in December reached Rp179.147.340,00. Capital that should be provided to anticipate unexpected loss called by Economic Capital. Economic Capital period in December 2012 based on VaR confidence level 99% reached Rp173.258.550,00.Mitigation strategy of murabahah financing risk in BMT XYZ Surabaya classified into two kinds, they are proactive risk strategy and reactive risk strategy. Proactive risk strategy performed by analyzing the character, financial capability, and collateral of prospective customer. Reactive risk strategy performed by silaturahim approach, rescheduling andrestructuring, and last withdrawal guarantees.This research suggests that there are several actions to mitigate credit risk that need to be added BMT XYZ Surabaya such as: 1. Implementation measurement financing risk using VaR approach, 2. Analyze capital and condition of prospective borrower, and 3. Implementation reconditioning to recovery financing problems.